Development of ternary nanocomposite for civil constraction and fabrication of process vessels - Olalekan, Salawudeen Taofeeq; Muyibi, Suleyman Aremu; Al-Khatib, Ma'an Fahmi Rashid; Yusof, Faridah; Shah, Qasim Hussain; Qudsieh, Isam Y. (2010)
Introduction: Polymer reinforced with Carbon Nanotubes and Nanoclay are receiving research attention for various industrial applications such as automobile interior and exterior accessories, air and space craft, electronics, civil constructions and fabrications of process vessels Problem Statement: Current researches have shown that the thermoplastic-clay nanocomposites have failed to live up to the earlier predictions albeit they have found some niche area of applications. This research work therefore aimed at studying the effect of carbon nanotube as secondary filler on the mechanical properties of polypropylene-clay nanocomposite. Approach: Hybrid polypropylene-clay nanocomposite was prepared in the presence of multiwall carbon nanotubes (MWCNTs) as secondary additives using melt intercalation process. ..